Interaction network of ABA receptors in grey poplar. (4th September 2017) - Papacek, Michael; Christmann, Alexander; Grill, Erwin
Significance Statement: The plant hormone abscisic acid (ABA) is a key player in responses to abiotic stress. The study analyzes the combinatorial interaction of ABA receptors and co‐receptors from poplar. Functional characterization of the receptor complexes and heteromeric receptor complexes of poplar and Arabidopsis show high conservation of the receptor components between an annual and a perennial plant. Summary: The plant hormone abscisic acid (ABA) is a key player in responses to abiotic stress. ABA regulates a plant's water status and mediates drought tolerance by controlling stomatal gas exchange, water conductance and differential gene expression. ABA is recognized and bound by the Regulatory Component of ABA Receptors (RCARs)/PYR1/PYL (Pyrabactin Resistance 1/PYR1‐like). Ligand binding stabilizes the interaction of RCARs with type 2C protein phosphatases (PP2C), which are ABA co‐receptors. While the core pathway of ABA signalling has been elucidated, the large number of different ABA receptors and co‐receptors within a plant species generates a complexity of heteromeric receptor complexes that has not functionally been resolved in any plant species to date. In this study, we characterized ABA receptors and co‐receptors of grey poplar ( Populus x canescens [Ait.] Sm.) and their capacity to regulate ABA responses. We observed a high number of regulatory combinations of holo‐receptor complexes, but also some preferential and selective RCAR–PP2C interactions. Poplar and Arabidopsis ABA receptor components revealed a strong structural and functional conservation. Heterologous receptor complexes of poplar and Arabidopsis components showed functionality in vitro and regulated ABA‐responsive gene expression in cells of both species. ABA‐responsive promoters of Arabidopsis were also active in poplar, which was explored to generate poplar reporter lines expressing green fluorescent protein in response to ABA. The study presents a detailed analysis of receptor complexes of a tree species and shows high conservation of ABA receptor components between an annual and a perennial plant.